Температура кожи и ее топография у некоторых видов птиц - Лысов, Е.С. (Вестник зоологии, 1969)
The results are presented of the investigation concerning skin temperature and its topography in thirty species of birds in captivity. The maximum skin temperature is observed in the following species: in Falconiformes on the surface of big pectoral muscle— —39 3°, in Passeriformes — on the back and between the wings —41.2°, in Strigiformes on the abdominal part of the body —40.8°, in Charadriiformes under the wing —40.5°, in Galliformes (Coturnix coturnix) on the surface of big pectoral muscle and under the wing —40.0°, in Coraciiformes (Coracias garrulus) — on the surface' of big pectoral muscle —39.2°. The distribution of skin temperature is connected with the peculiarities of the species thermoregulation.